Dynamics and necessity of SIRT1 for maternal-zygotic transition - Nevoral, Jan; Drutovic, David; Vaskovicova, Michaela; Benc, Michal; Liska, Frantisek; Valentova, Iveta; Stachovicova, Sara; Kubovciak, Jan; Havrankova, Jirina; Shavit, Miki; Monsef, Ladan; Iniesta-Cuerda, Maria; et al. (Scientific reports, 2024)
Dynamic changes in maternal‒zygotic transition (MZT) require complex regulation of zygote formation, maternal transcript decay, embryonic genome activation (EGA), and cell cycle progression. Although these changes are well described, some key regulatory factors are still elusive. Sirtuin-1 (SIRT1), an NAD+-dependent histone deacetylase, is a versatile driver of MZT via its epigenetic and nonepigenetic substrates. This study focused on the dynamics of SIRT1 in early embryos and its contribution to MZT. A conditional SIRT1-deficient knockout mouse model was used, accompanied by porcine and human embryos. Embryos across mammalian species showed the prominent localization of SIRT1 in the nucleus throughout early embryonic development. Accordingly, SIRT1 interacts with histone H4 on lysine K16 (H4K16) in both mouse and human blastocysts. While maternal SIRT1 is dispensable for MZT, at least one allele of embryonic Sirt1 is required for early embryonic development around the time of EGA. This role of SIRT1 is surprisingly mediated via a transcription-independent mode of action.
Keywords: Sirtuin 1; Zygote; Humans; Blastocyst; histony; embryonální vývoj; zygota; Female; lidé; zvířata; myši; Mice; Swine; myši knockoutované; Gene Expression Regulation, Developmental; blastocysta; Embryonic Development; ženské pohlaví; Male; Mice, Knockout; Histones; embryo savčí; vývojová regulace genové exprese; Animals; sirtuin 1; mužské pohlaví; prasata; Embryo, Mammalian